Management of Otomycosis in Pregnancy: A Case Study - Fierda Ovita Azhari; Gustav Syukrinto (Jurnal Sehat Indonesia (JUSINDO), 2026)
Otomycosis is a fungal infection of the external auditory canal that commonly occurs in tropical and humid regions such as Indonesia. Pregnancy is a unique physiological condition characterized by hormonal and immunological changes that may increase susceptibility to fungal infections while simultaneously limiting therapeutic options due to concerns regarding fetal safety. This report details the clinical management of a 25-year-old pregnant patient (G1P0A0) at 24 weeks gestation who presented with complaints of severe pruritus and aural fullness in the right ear.  Clinical examination revealed characteristic fungal debris with a "white fluffy" appearance. Management included aural toilet followed by the topical solution, a treatment selected for its high efficacy and established safety during pregnancy. The successful resolution of the infection without maternal or fetal complications reinforces the efficacy of combined mechanical debridement and topical therapy. This case underscores the importance of specialized ENT care in secondary referral hospitals for managing infections in high-risk populations.